A Topologia e o 'Fold': Contributos à Forma Contemporânea - Frederico Guilherme Tavares Pinho Martins (2018)
The theorectical debate is contemporarily centered, among other aspects, in managing complexity in architecture. This discussion goes back to one other, started five decades ago and focused on the idea of "conflict" and "contradiction" as an architectural response to the heterogeneous, diverse and differentiated cultural context. Now, its normative principles, nourished by the evolution of cientific and theoretical contents, find in the new systemic theories and substantially in their topological attributes an alternative to such strategies as an operative model to architecture. The following paper explores the sustained relationship between topology and the morphosyntactic and design dimensions in architecture. Such exercise, focused on the postcontradictory aesthetics of the deleuzian fold, aims to inquire the architectural productivity of the topological geometries which replace combinatorial logics of platonic forms by other principles systematizing time, connection and flexibility. First, it exposes the evolution of Geometry, framing certain concepts and values convergent to the topological theme. While doing so, it also stresses the relationship between geometry and the evolution of the morphological landscape of architecture. Afterwards, it traces the correlation between the specificities of the topological discipline and the plasticity of Gilles Deleuze's discourse, drawing, at last, the architectural substance of those issues particularly regarding its productivity on the architectural thought and in morphological and morphogenetic explorations within the performative and relational realm of architecture.